Methicillin Resistant Staphylococcus aureus Contamination of Hands and Mobile Phones of Health Care Workers in a Health Care Setting: A Silent Threat - B.K. Sharma; S.M. Regmi; K. Sharma; K.R. Reddy; S. Adhikari (Journal of Gandaki Medical College, 2019)
Background: The extensive use of mobile phones in the hospital among health care workers (HCWs) can lead to infectious agents being transferred from one patient to another and thus serve as a vehicle in the transmission of nosocomial pathogens.